Organisational kindness and compassion: what are the barriers, enablers and outcomes for clients and stakeholders? - Jennifer Smith-Merry; Damian Mellifont; Justin Newton Scanlan; Nicola Hancock (PLoS ONE, 2025)
Unkind bureaucratic policies such as the Australian Robodebt policy, which targeted welfare recipients with automatic debt letters, and are geared towards economic savings, can significantly harm those impacted by them. Compassion and kindness are receiving increased research attention related to how organisations work internally. However, a greater investment in studies is needed to increase understandings about how compassion and kindness can underpin interactions with external stakeholders. Addressing this research gap, we aimed to identify barriers, enablers and outcomes to organisational kindness and compassion informed by the literature, and to propose future research directions related to organisational kindness and compassion towards external stakeholders. A search of four scholarly databases identified 25 relevant publications. Thematic analysis of included publications revealed barriers of commodification, personal risks, dysfunctional environments, inauthentic attempts at, and a lack of understanding of the need to be compassionate or kind. Enablers included building compassion into organisational policies, processes, practices and activities, compassion contagion, training of staff, leading with compassion, and kind and compassionate communication. Outcomes of kindness included building positive and healthy relationships with stakeholders, supporting positive experiences among stakeholders, and contributing to an organisation’s profitability, productivity, performance and standing in the community. We conclude by recognising that kindness is essential for ongoing trust in health and social care institutions and government policy.